The sweet quartet: binding of fucose to the norovirus capsid - Koromyslova, Anna D.; Leuthold, Mila; Bowler, Matthew W.; Hansman, Grant S. (Virology, 2015)
Human noroviruses bind histo-blood group antigens (HBGAs) and this interaction is thought to be important for an infection. We identified two additional fucose-binding pockets (termed fucose-3/4 sites) on a genogroup II human (GII.10) norovirus-protruding (P) dimer using X-ray crystallography. Fucose-3/4 sites were located between two previously determined HBGA binding pockets (termed fucose-1/2 sites). We found that four fucose molecules were capable of binding altogether at fucose-1/2/3/4 sites on the P dimer, though the fucose molecules bound in a dose-dependent and step-wise manner. We also showed that HBGA B-trisaccharide molecules bound in a similar way at the fucose-1/2 sites. Interestingly, we discovered that the monomers of the P dimer were asymmetrical in an unliganded state and when a single B-trisaccharide molecule bound, but were symmetrical when two B-trisaccharide molecules bound. We postulate that the symmetrical dimers might favor HBGA binding interactions at fucose-1/2 sites.
Gesehen am 22.07.2020